Ieme Van der Poel. New Literary Voices of the Moroccan Diaspora: Republic of Cousins. Liverpool UP, 2022. - Hanan Elsayed (Studies in 20th & 21st Century Literature, 2025)
Review of Ieme Van der Poel, New Literary Voices of the Moroccan Diaspora: Republic of Cousins. Liverpool UP, 2022. 213 pp.
Keywords: Moroccan diaspora